Public Service: Digital Transformation Building Smart City In Makassar City - Maldun, Syamsuddin; Juharni, Juharni; Ridho, Muhmmad; Anas, Ali; Afrisal, Ade ferry (International Journal of Artificial Intelligence Research, 2024)
The demands of the era of globalization of modern government systems require the management of changes in district/city governments to improve so that stakeholders can access maximum service. For this, an applicable work mechanism is needed through the design of a prototype model of Digital Transformation of Public Services e-Government. The type of research used is phenomenological and qualitative descriptive approach. The data collection method used is triangulation, namely: survey, interview, and document analysis. Data analysis uses data collection, data condensation, data presentation, verification and drawing conclusions. Research results: focus (1) The reality of the institutional structure and human resources of the Communication and Information Service still experiences various challenges and weaknesses that must be anticipated immediately, (2) Determinant factors in capacity development originating from internal sources, namely publication, polling up, and decision-making and external opportunities supported by the local government. Meanwhile, internal obstacles are the still strong interests of political parties and external challenges are that public participation is still lacking, and (3) Prototype model of Digital Transformation of Public Services e-Government, is actually a public right and at the same time an obligation of the government, Management of existing public services system, separately accommodates data exchange between institutions, and Management of public services according to regulations, which are guided by Law 37/2008, Law 25/2009 and Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform 27/2014 is a combination of complementary nomenclature.